Postural risk assessment of mechanised firewood processing. Issue 3 (4th March 2017) - Spinelli, Raffaele; Aminti, Giovanni; De Francesco, Fabio
Abstract: The study assessed the postural risk of mechanised firewood processing with eight machines, representing the main technology solutions available on the market. Assessment was conducted with the Ovako Working posture Analysis System (OWAS) on 1000 still frames randomly extracted from videotaped work samples. The postural risk associated with firewood processing was variable and associated with technology type. Simple, manually operated new machines incurred a higher postural risk compared with semi- or fully automatic machines. In contrast, new semi-automatic and automatic machines were generally free from postural risk. In all cases, attention should be paid to postural risk that may occur during blockage resolution. The study did not cover the postural risk of firewood processing sites as a whole. The study provided useful information for selecting firewood processing machinery and for improving firewood machinery design, as part of a more articulate strategy aimed at enhancing the safety of firewood processing work sites. Practitioner Summary: The postural risk associated with mechanised firewood processing (eg cutting and splitting) depends on the type of equipment. Postural risk is highest (OWAS Action Category 2) with new in-line machines, designed for operation by a single worker. Fully automatic machines present minimum postural risk, except during blockage resolution.